Memory bias for threatening information related to anxiety: an updated meta-analytic review. Issue 7 (3rd October 2017) - Herrera, Sara; Montorio, Ignacio; Cabrera, Isabel; Botella, Juan
ABSTRACT: The evidence for an anxiety-related memory bias is contradictory. We compiled 171 articles published until October 2016 including a group with clinical or subclinical anxiety and a control group in tasks involving implicit or explicit memory using threatening stimuli. There was an anxiety-related memory bias in free recall tasks, but it was not observed in another memory task. The between-groups differences showed that the anxious group recalled more threatening stimuli than the control group ( d  = 0.321). When we compared the group differences (anxious vs. control participants) in the within-groups effect (threatening vs. neutral stimuli), a moderate effect size emerged ( d bw  = 0.714). This anxiety-related memory bias was observed with shallow processing, that is consistent with attentional biases related to anxiety. There was also evidence that high-anxious persons recall fewer positive stimuli. Future research is needed to investigate whether this result is a memory or encoding bias and explore other moderator variables.